Translation of Character Names in Le avventure di Pinocchio by Carlo Collodi - Lukančenko, Brigita; Klioštoraitytė, Rasa (Vertimo studijos, 2020)
Translating character names in fiction can be difficult, as names can perform different functions: not only naming, but also highlighting characteristic features. Translators of fiction have to make certain decisions how to render names in the Target Text and retain the functions and meanings they serve in the Source Text. The aim of this article is to analyse the translation of character names in C. Collodi’s Le avventure di Pinocchio into Lithuanian, Polish and Russian and to compare the translation startegies chosen by the translators. The results of this analysis show that the most common rendering method in the Lithuanian, Polish and Russian versions was direct translation. Also, it can be concluded that character names were rendered most accurately in their translation into Lithuanian, the second in terms of accuracy of rendering character names is the translation into Russian, and the third – into Polish.